Yellow Fever Outbreak in Brazil: A crucial time for epidemiologic surveillance - Siqueira, Priscila Carminati; de Souza, Fernanda Mattos; Alves, Caroline Gava; Sanchez, Mauro Niskier; Noia Maciel, Ethel Leonor; do Prado, Thiago Nascimento (Revista de Epidemiologia e Controle de Infecção, 2019)
Brazil lived a crucial time for public health and epidemiologic surveillance on the fight against yellow fever (YF) during 2016/2017, mainly in southeastern states where the greatest population concentration occurs, the most economically developed region of the country. In this letter, we show some epidemiologic data from that outbreak and we discussion that crucial time for epidemiologic surveillance